Kontribusi Pemikiran Egbert Schuurman mengenai Permasalahan dan Solusi Teknologi Modern - Adrian Jonathan (Reformed Center for Religion and Society, 2015)
ABSTRACT:In the modern technological world, human is constantly relating with technology, be it as a user or as a part of technological production mechanism. But what is technology, what kind of value that technology brings, and how should one response to technology? Does technology brings good, bad or neutral? These are the questions that we need to answer as we live in a technological world. In the philosophy of technology, there is one thinker, who represents the school of Reformational Philosophy, named Egbert Schuurman. In the midst of two kinds of reaction towards technology (optimistic and pessimistic) Schuurman proposes a Liberating Perspective as the third option. This perspective is aware of the deep influence of human sinfulness in technological development. However, it also considers the beauty of creational design and Christ’s redeeming power for technological development. In this article, the writer would like to observe Schuurman’s thoughts regarding this Liberating Perspective as a considerable solution to the problems of modern technological life. KEY WORDS: technology, modern, society, reformational philosophy, liberating perspectives, responsible ethics